Isolation and characterization of tocopherol cyclase cDNA sequence from oil palm - Lai, Mun Seong; Abdullah, Siti Nor Akmar; Ho, Chai Ling; Abdul Aziz, Maheran (2009)
Palm oil which contains equal proportion of saturated and monounsaturated fatty acids have turned into an asset in view of current dietary recommendations. Additionally, a wide range of natural palm oil minor components, differing in their physicochemical characteristics is an important attribute. The minor components constitute less than 1% of palm oil content and their contribution towards human nutrition has been reviewed extensively recently. The most notable is the vitamin E (tocopherol and tocotrienol). There is now a growing interest in the nutritional and medical benefits of vitamin E in palm oil, especially, the antioxidant activities, cholesterol lowering and anti-cancer effects. Therefore, research on the molecular mechanism regulating biosynthesis of vitamin-E in oil palm is of interest. Earlier findings suggest that elevated tocopherol cyclase (TC) can increase the plant final tocopherol content. For further understanding the gene expression profile of TC in oil palm, absolute quantification real-time PCR was performed using 10 chosen oil palm tissues. Primer set was designed based on the 3’UTR region to increase the specificity of amplification. The real-time PCR result shows that the expression of TC was moderately low at the beginning of mesocarp fruit developmental stages. Highest expression was observed at mesocarp tissues at 17 weeks after anthesis (w.a.a), then start diminishing during late stages of fruit ripening. We have also successfully isolated the full-length mature protein cDNA sequence which showed strong homology to Oryza sativa (AP008208) of 79%, Eucalyptus gunnii (AY336944) of 77%, Vitis vinifera (A7P598) of 77%, Zea mays (Q94FY8) of 77%, and Helianthus annus (DQ229848) of 73%. These results provide an insight about the regulation of TC within different oil palm tissues which is useful for designing future genetic improvement strategy of oil palm.